Prevalence and risk factors of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) carriage in Asia-Pacific region from 2000 to 2016: A systematic review and meta-analysis - Wong,JWH; Ip,M; Tang,A; Wei,VWI; Wong,SYS; Riley,S; Read,J; Kwok,KO (Clinical Epidemiology, 2018)
Objective: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) is an emerging global public health threat. In response to a highlighted strategic priority of the World Health Organization Global Action Plan on Antimicrobial Resistance, to “strengthen the knowledge and evidence base through surveillance and research”, we synthesized published articles to estimate CA-MRSA carriage prevalence in the Asia-Pacific region.Methods: A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PROSPERO CRD:42017067399). We searched MEDLINE, EMBASE, and PubMed for articles published from 1 January 2000 to 19 May 2017, which reported CA-MRSA carriage (defined as either colonization or infection) in Asia-Pacific region from 2000 to 2016. Studies were stratified according to settings (community or hospital where CA-MRSA was isolated) and study populations (general public or subpopulations with specified characteristics). Ranges of CA-MRSA carriage prevalence were reported for study groups.Results: In total, 152 studies were identified. Large diversity was observed among studies in most study groups. In community-level studies, the CA-MRSA carriage prevalence among the general public ranged from 0% to 23.5%, whereas that ranged from 0.7% to 10.4% in hospital settings. From community-level studies, countries with the highest prevalence were India (16.5%–23.5%), followed by Vietnam (7.9%) and Taiwan (3.5%–3.8%). Children aged ≤6 (range: 0.5%–40.3%) and household members of CA-MRSA carriers (range: 13.0%–26.4%) are subgroups without specific health conditions but with much higher CA-MRSA carriage when compared to the general population.Conclusion: Our CA-MRSA prevalence estimates serve as the baseline for future national and international surveillance. The ranges of prevalence and characteristics associated with CA-MRSA carriage can inform health authoritie